Sphingomyelin-induced glucocorticoid receptor alterations lead to impaired presynaptic plasticity in acid sphingomyelinase deficient neurons - Sara Naya-Forcano; Ángel Gaudioso; Beatriz Soto-Huelin; Celia García-Vilela; César Venero; Edward H. Schuchman; José A. Esteban; María Dolores Ledesma (Neurobiology of Disease, 2025)
Acid sphingomyelinase deficiency (ASMD) is a rare disease caused by mutations in the gene encoding ASM, an enzyme that degrades sphingomyelin (SM). In addition to SM accumulation, neuroinflammation and cognitive impairment are pathological hallmarks of neurovisceral ASMD. Since the glucocorticoid system may influence these features, we have characterized it in ASM knockout (ASMko) mice that mimic this form of the disease. While plasma corticosterone levels are not altered in these mice, brain levels of the α, but not the β, isoform of glucocorticoid receptors (GR) are reduced. The reduction is evident in neurons and is due to the accumulation of SM. As a consequence, the expression of the protein, synapsin I, is low in ASMko neurons, leading to the disorganization of synaptic vesicles and to impaired presynaptic plasticity. Treatment with the glucocorticoid hydrocortisone diminished SM levels, increased synapsin I expression, and improved presynaptic function in neuronal cultures and hippocampal slices of ASMko mice. These findings establish, for the first time, a link between the glucocorticoid system and brain pathology in ASMD, highlighting the GR as a potential therapeutic target for this devastating disease.